+0  
 
0
246
1
avatar

f(x) = -2x + m,      f(-3) = 3f(0) 

 

I'm having trouble figuring out the second part.  f(-3) = 3f(0) <- how do you calculate that number? 

Guest Oct 22, 2014

Best Answer 

 #1
avatar+17721 
+5

f(x)  =  -2x + m

f(-3)  =  -2(-3) + m  =  6 + m

f(0)  =  -2(0) + m  =  m

Since  f(-3)  =  3·f(0)                    Substitute the values found above to get:

--->  6 + m  =  3[m]

         6 + m  =  3m

                6  =  2m

                m  =  3

geno3141  Oct 22, 2014
Sort: 

1+0 Answers

 #1
avatar+17721 
+5
Best Answer

f(x)  =  -2x + m

f(-3)  =  -2(-3) + m  =  6 + m

f(0)  =  -2(0) + m  =  m

Since  f(-3)  =  3·f(0)                    Substitute the values found above to get:

--->  6 + m  =  3[m]

         6 + m  =  3m

                6  =  2m

                m  =  3

geno3141  Oct 22, 2014

17 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details